The Habituation of Tarbawi Pedagogy in Teaching Akidah Akhlak - Hamad Rojali (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to examine the habituation of moral education through Akidah Akhlak lessons at MTS Muallimin UNIVA Medan and its impact on students’ ethical behavior. Using a qualitative approach, data were collected through semi-structured interviews, observations, and documentation involving key informants, including teachers, the head of the madrasah, and students, supported by secondary sources such as books, theses, websites, and media reports. Data analysis was conducted through triangulation to ensure validity and reliability. The findings indicate that teachers’ role modeling, structured practice of ethical behaviors in daily school routines, and collaboration with parents and supportive facilities collectively foster students’ internalization of Akhlak values. Observable behaviors include neat uniform, punctuality, respect toward teachers and peers, diligence in learning, completion of assignments, and adherence to school rules. These results demonstrate that sustainable habituation of ethical education, grounded in Tarbawi pedagogy, effectively develops students’ moral character and prepares them to apply these values in broader societal contexts.